K8[Mo4S4(CN)12]·4H2O: A New Alternative Synthetic Route for its Formation by Core Conversion from Trimer to Tetramer - Sah, Ramjee; Sah, Balramjee (Asian Journal of Chemistry, 2013)
For the first time the conversion of trimeric (M3S4)4+ to tetrameric (M4S4)4+ core has been made for molybdenum complex. The complex, K5[Mo3S4(CN)9] (1) on using with strong reducing agent transform into K8[Mo4S4(CN)12] (2) in near quantitative yield. The diamagnetic complex (1) containing (Mo3)6 core can accommodate two electrons in its non bonding molecular orbital 2a1 under reducing environment to give a complex ion [Mo3S4(CN)9]7- with [Mo3]8 electronic configuration. This reduced species undergoes re-oxidation by atmospheric air to give back the original compound with [Mo3]6 core via a partially oxidized an intermediate species [Mo3S4(CN)9]6- with [Mo3]7 core shows a characteristic EPR signal. However, under drastic reducing condition, the two electrons reduced species [Mo3S4(CN)9]7- with [Mo3]8 core accommodate the next coming electron to its anti-bonding two electron orbital and thus achieve an unstable trinuclear [Mo3III]9 core, where each metal centre has been reduced by one electron. The highly unstable and super reduced species [Mo3S4(CN)9]8- with [Mo3III]9 configuration undergoes core transformation from cuboidal trinuclear [Mo3IVS4]4+ to the cubane type tetranuclear core [Mo4IIIS4]4+ of [Mo4S4(CN)12]8- complex ion. The corresponding tungsten-analogue though responses this reduction, but quickly oxidizes back to the starting material during work-up procedure.